Volume 3: Modeling and Validation; Multi-Agent and Networked Systems; Path Planning and Motion Control; Tracking Control System 2018
DOI: 10.1115/dscc2018-9048
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Dynamics Analysis of a Beam-Hoverboard Self-Transportation System

Abstract: In recent years, self-balancing personal transportation devices have gained significant popularity, the most popular ones being the “Hoverboard” systems. These systems utilize the dynamics of an inverted pendulum to create stable lateral motion. In this paper, the dynamic behavior of a hoverboard system with an attached flexible beam is investigated. By introducing a flexible beam, the vibrational characteristics of the system created by both the rider and the environment can be measured and accounted for. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…( 24)-(33), it is sufficient to omit the ϕ and one of these beams. Then, the final equations will convert to [23].…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…( 24)-(33), it is sufficient to omit the ϕ and one of these beams. Then, the final equations will convert to [23].…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The first idea of using flexible structure as an inverted pendulum in robot was created by Nguyen et al They studied a linearized mathematical model and controller for a single flexible inverted pendulum, this model only accounted for lateral movement in one direction rather than in the two directions and it has four wheels [22]. In another robot Mehrvarz et al modeled a two-wheeled flexible inverted pendulum which can move in one direction [23]. They also designed a MPC controller for their robot and showed that the percision of their modeling [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many flexible systems are modeled using a linear PDE and a set of BCs. To achieve the control purposes of flexible structures, most engineers rely on discretizing the governing PDE into a set of ordinary differential equations (ODEs) [4], [34], [35]. This is because of the abundance of control design techniques available for ODEs and mathematical complexities of boundary control of PDE models.…”
Section: Controller Designmentioning
confidence: 99%
“…One of the important continuous systems in mechanical engineering is the micro-beam. Micro-beams have many applications in transportation [4], MEMS and NEMS [5],atomic force microscopy (AFM) [6], micro switches [7]- [10], mass sensors, micro-accelerometers, micro-mirrors [11], [12], grating light valves (GLV) [13]- [15] and cell contraction assays [16].…”
Section: Introductionmentioning
confidence: 99%